Prevalence of Depression among elderly living in old age homes of Kathmandu Valley and its association with Sociodemographic variants - Kafle, B.; Sharma, V.D.; Ojha, S.P.; Chapagain, M; Tulachan, P.; Dhungana, S. (Journal of Psychiatrists’ Association of Nepal, 2017)
Introduction: There has been a considerable increase in the numbers of older people in the world population of both developed and developing countries. The increasing elderly populations are prone to depression. Studies regarding depression among elderly, especially in old age homes is lesser in the developing countries. Objectives: To estimate prevalence of depression among elderly living in old age homes in Kathmandu valley and its association with the socio-demographic variables, individual factors and environmental factors. Method: It is a cross sectional study where 203 elderly people residing in old age homes of Kathmandu Valley, Nepal were selected randomly. Interview was carried out using socio-demographic tool, Geriatric Depression Scale (GDS), ICD-10 DCR, Duke social support scale, UCLA loneliness scale, and Barthel index was used. Results: This study showed that, 47.3% of population had depression. Among them, 34.0% had mild depression and 13.3% had severe depression. There was significant association between the prevalence of depression, health problems, satisfaction with old age home, loneliness, social support and functional disability. Conclusion: Depressive disorder is highly prevalent among the elderly population residing in old age homes in Kathmandu Valley. This results in lowering their productivity and places burden to family and society. For this reason, concerned authorities should timely address depression in elderly people.